Modeling diffusion mass transport in multiphase polymer systems for gas barrier applications: A review. Issue 8 (10th January 2018) - Zid, Sarra; Zinet, Matthieu; Espuche, Eliane
ABSTRACT: Polymer nanocomposites offer a great interest as gas barrier materials because of their much‐enhanced properties arising from the nanoparticles shape, size, and spatial arrangement within the matrix. However, optimization and further development of such materials requires fundamental understanding of the influence of the nanocomposite structure on permeating gas diffusion. This step can be greatly facilitated through modeling/simulation strategies able to establish relationships between the material microstructure and the achieved enhancement of barrier properties. This review first presents the analytical models developed to estimate the effective diffusivity in polymer nanocomposites. The predictions of the models are analyzed with respect to experimental data reported in the literature and their ability to describe accurately the nanocomposite transport properties when the microstructure complexity increases is discussed. Then, modeling approaches based on numerical simulation techniques (e.g., the finite element method) that allow simulating the diffusion processes and assessing the effect of filler shape, orientation, dispersion, and spatial arrangement are reviewed and discussed. Finally, the importance of 3D simulation strategies for the understanding and prediction of transport properties in the most complex nanocomposite microstructures is addressed. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 621–638 Abstract : Understanding the impact of the nanocomposite structure on gas diffusion is crucial for barrier applications. In this review, the analytical approaches developed to model the gas transport in nanocomposites are analyzed with respect to experimental data. Their ability to describe materials with increased complexity is also discussed, as well as approaches based on numerical simulation techniques (e.g., the finite element method). Finally, the review addresses the interest of 3D simulation strategies to model complex structure.